Experimental Comparative Performance Analysis of Li-Po and Li-Ion Batteries Using Telemetry-Based Flight Testing in Fixed-Wing UAV for KRTI LELA Mission - Tadeus Ferdinan Dato Odja; Muhamad Syariffuddien Zuhrie; Agus Wiyono; Fendi Achmad; Sayyidul Aulia Alamsyah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The Indonesian Flying Robot Contest (KRTI) Long Endurance Low Altitude (LELA) division evaluates fixed-wing Unmanned Aerial Vehicles (UAVs) not only based on endurance, but also on mission completion speed, where faster completion yields additional scoring points. This study aims to analyze and compare the performance characteristics of Lithium-Polymer (Li-Po) and Lithium-Ion (Li-ion) batteries in fixed-wing UAV operations and to evaluate their suitability based on competition-oriented mission strategies. An experimental approach was employed by conducting flight tests under identical UAV configurations, autonomous waypoint trajectories, flight altitudes, and termination voltage limits to ensure consistency. The evaluated parameters include voltage behavior, average current consumption, flight duration, cruising speed, and distance traveled. The results indicate that the Li-Po battery achieved a longer flight duration of 51 minutes with a lower average current of 18.82 A and a cruising speed of 25 m/s, demonstrating stronger endurance capability. Conversely, the Li-ion battery exhibited a shorter flight duration of 39 minutes but operated at a higher cruising speed of 32.5 m/s with an average current of 30.77 A, enabling a longer travel distance of 68.4 km compared to 64.5 km for the Li-Po battery. These findings highlight a significant trade-off between endurance and mission completion speed. The study confirms that battery selection in fixed-wing UAV operations for KRTI LELA should be aligned with mission scoring priorities rather than focusing solely on endurance. Furthermore, this research contributes to UAV energy system optimization by experimentally demonstrating the interaction between battery characteristics and operational strategies in determining mission performance outcomes.